High School Students Chemistry Learning Skills: Empirical Studies on Lombok Island - Junaidi, Eka; Anwar, Yunita Arian Sani (Jurnal Inovasi Pendidikan IPA, 2024)
This study aims to assess the chemistry learning skills of high school students on the island of Lombok. Our study evaluated gender, grade level, learning style, learning interest, school location, and school status in students' chemistry learning skills with the researcher's instrument. This descriptive study involved 467 students from four districts/cities on Lombok Island. The questionnaire has thirty statements into five dimensions: responsibility, organization, independent work, collaboration in group work, and initiative. Empirical data were analyzed using ANOVA, LSD, and Scheffe's test. The results showed that gender, grade level, learning style, interest in learning, and school status significantly affected students' chemistry learning skills. However, school location showed little difference in all the skills dimensions measured.